Agama dan Benturan Peradaban - Syarifuddin Syarifuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
The presence of religion, especially the religions of mission, in human life has  established a separate civilization characteristics which can lead to a clash of civilization  which is assumed in the form of inter-group conflict of civilizations. The clash believed to be a  necessity is mainly triggered by modernity which in the end led to the secularization. The  above assumptions initiated by Huntington still can be criticized for several reasons. However,  the tolerance between civilizations should be implemented. In this regard, multiculturalism as  the willingness to accept other groups equally as an entity regardless of cultural differences,  ethnicity, gender, language, religion or country becomes important to be discussed. Likewise, vertical and horizontal dialogue should be the most essential way to cultivate harmonious life  among all religious people.